Book Review: Global Indigenous Health: Reconciling the Past, Engaging the Present, Animating the Future - Battiston, Chris (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
Literature about Indigenous health has dramatically increased over the past few years, which has made it difficult to stay current—this is a good thing. This uptick indicates that this work is getting attention it deserves. However, every so often a collection comes along that provides an essential overview of the work being done, and Global Indigenous Health: Reconciling the Past, Engaging the Present, Animating the Future is one such book. It examines the impacts and effects of health determinants on Indigenous Peoples from across the globe, including Micronesia, Alaska, and Canada.